The development of students’ performance abilities in learning guitar at the faculty of Arts - Касілов, Іван Анатолійович (Pedagogy of Higher and Secondary Education, 2015)
Kasilov I. А. The development of students’ performance abilities in learning guitar at the faculty of Arts. The article deals with the main problems of formation and development of performance technique as well as the common professional level in playing six-string classical guitar in the context of educational program in Ukraine. The historical features of musical instrument appearance are given as well as the methodical ways for the solution of the main performing problems are considered.